Understanding facilitators and barriers of direct‐acting antiviral therapy for hepatitis C virus infection in prison. Issue 12 (19th September 2018) - Lafferty, Lise; Rance, Jake; Grebely, Jason; Lloyd, Andrew R.; Dore, Gregory J.; Treloar, Carla; ,
Summary: Hepatitis C virus (HCV) infection is a major public health concern. Globally, 15% of those incarcerated are HCV‐antibody positive (anti‐HCV). Even where HCV treatment is available within prisons, treatment uptake has remained low. This qualitative study was conducted to understand the barriers and facilitators for the delivery of HCV treatment in prisons from the perspectives of prisoners. This is important to inform health messaging for HCV treatment within correctional institutions. Thirty‐two prisoners (including eight women) with a history of injecting drug use participated in this qualitative study. Participants were equally recruited across four correctional centres (n = 8 per site). Overall, 16 participants (50%) had chronic HCV at their most recent test, and two participants were awaiting test results at time of interview. Structural (eg proximity of health clinic) and patient‐level (routine and motivation) factors were viewed as facilitators of HCV treatment within the prison setting. Structural (eg risk of reinfection) and social (eg lack of confidentiality and lack of social support) factors were perceived as barriers to prison‐based HCV care and treatment. In conclusion, to increase HCV treatment uptake, prison‐based programmes should implement (or advocate for) patient‐centred treatment approaches that protect privacy, provide social support, and promote access to clean needles and substitution therapy to protect prisoners from reinfection.